2020
DOI: 10.1186/s12936-020-03524-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of pfdhfr and pfdhps mutations associated with sulfadoxine–pyrimethamine resistance in Plasmodium falciparum isolates from Jazan Region, Southwestern Saudi Arabia: important implications for malaria treatment policy

Abstract: Background Despite significant progress in eliminating malaria from the Kingdom of Saudi Arabia, the disease is still endemic in the southwestern region of the country. Artesunate plus sulfadoxine–pyrimethamine (AS + SP) has been used in Saudi Arabia since 2007 as a first-line treatment for uncomplicated Plasmodium falciparum malaria. This study aimed to investigate the prevalence of mutations associated with resistance to artemisinin and sulfadoxine–pyrimethamine (SP) resistance in P. falcipar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Hence, it seems that, unless there are appropriate measures in place, the construction of dams for irrigation and hydroelectric generation could intensify malaria transmission by providing breeding habitats for prominent malaria vector species, especially in areas of unstable or limited transmission [ 18 , 39 ]. In addition, increased cross-border importation of malaria [ 34 ] and poor awareness of malaria prevention measures among the general population [ 40 ], as well as the emerging resistance of the parasites to treatment and the resistance of the vectors to insecticides might also have contributed to this outbreak [ 19 ]. Therefore, this malaria outbreak indicates that there is a need for rigorous impact assessments of metrological and climate change-related variables as well as dam-related environmental factors in Jazan region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it seems that, unless there are appropriate measures in place, the construction of dams for irrigation and hydroelectric generation could intensify malaria transmission by providing breeding habitats for prominent malaria vector species, especially in areas of unstable or limited transmission [ 18 , 39 ]. In addition, increased cross-border importation of malaria [ 34 ] and poor awareness of malaria prevention measures among the general population [ 40 ], as well as the emerging resistance of the parasites to treatment and the resistance of the vectors to insecticides might also have contributed to this outbreak [ 19 ]. Therefore, this malaria outbreak indicates that there is a need for rigorous impact assessments of metrological and climate change-related variables as well as dam-related environmental factors in Jazan region.…”
Section: Discussionmentioning
confidence: 99%
“…stephensi , An . superpictus , and Anopheles culicifacies [ 18 , 19 ]. Although mosquitoes can be found throughout the year, the presence of Anopheles usually peaks following the rainy season that falls during October to December [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another study carried out in the Jazan region, southwestern Saudi Arabia, where artesunate plus sulfadoxine/pyrimethamine has been used since 2007 as a first-line treatment for uncomplicated P. falciparum malaria, investigated the prevalence of mutations associated with artemisinin and sulfadoxine/pyrimethamine resistance in the parasites circulating in this region. Polymorphisms in the propeller domain of the P. falciparum k13 (pfkelch13) gene and point mutations in the pfdhfr and pfdhps genes were identified by DNA sequencing [ 63 ]. Although no mutations were found in any of the 151 isolates in the pfkelch13 propeller domain, point mutations in pfdhfr and pfdhps genes were detected in 90.7% (137/151) of the isolates including double (N51I + S108N) and triple (N51I + C59R + S108N) pfdhfr mutations.…”
Section: Status Of Malaria Infection and Vector Control In Gulf Cooperation Council (Gcc) Countriesmentioning
confidence: 99%
“…Although drug resistance-conferring pfkelch13 mutations were not found, mutations in the pfdhfr and pfdhps genes were detected. The authors concluded that their observations undermine the efficacy of artemisinin-based combination therapy in the Jazan region in Saudi Arabia [ 63 ].…”
Section: Status Of Malaria Infection and Vector Control In Gulf Cooperation Council (Gcc) Countriesmentioning
confidence: 99%
“…In Saudi Arabia, CQ resistance was rst recorded in 1992 when reports on clinical treatment failures increased (Malik et al 1997;Alrajhi et al 1999;Al Arishi et al 2001). Subsequently, the malaria drug policy in the country was scaled up in 2007 and CQ was replaced with ACT, with artesunate plus SP as a rst-line treatment and artemether-lumefanthrine as the second-line for the treatment of uncomplicated falciparum malaria (Madkhali et al 2020;MOH 2018). Since then, some molecular studies have revealed a high prevalence of pfcrt 76T mutations in isolates from different areas of the country (Al Harthi, 2007; Bin Dajem and Al-Qahtani 2010; Bin Dajem et al 2012).…”
Section: Introductionmentioning
confidence: 99%